2018
DOI: 10.1080/16549716.2017.1419738
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a cluster randomised controlled trial on information technology-enabled nutrition intervention among urban adults in Chandigarh (India): SMART eating trial

Abstract: Nutrition is an important determinant of health. At present, nutrition programs in India mainly emphasize improving maternal and child nutrition. Adult nutrition has not received due attention, though diseases like hypertension and diabetes are largely preventable through changes in dietary and physical activity behaviour. Little is known about the best approaches to improve dietary behaviours, especially the role of modern information technology (IT) in health education. We describe the protocol of the SMART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…The trial was registered under the Clinical Trial Registry of India (CTRI/2016/11/007457; Date: 9/11/ 2016). The protocol paper with a detailed description of the study design and methodology has been published elsewhere [20].…”
Section: Trial Registrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial was registered under the Clinical Trial Registry of India (CTRI/2016/11/007457; Date: 9/11/ 2016). The protocol paper with a detailed description of the study design and methodology has been published elsewhere [20].…”
Section: Trial Registrationmentioning
confidence: 99%
“…The intervention was guided by the PRECEDE-PROCEED model [24], empirical literature on interventions, dietary guidelines by the National Institute of Nutrition, India [25], and qualitative formative research. A detailed description of the intervention protocol has been published elsewhere [20]. Qualitative formative research, guided by the Social Ecological Model, revealed multi-level influences on dietary behaviours at individual, family, and social-structural level which facilitated the development of context-specific, culturally acceptable intervention [26].…”
Section: Intervention Descriptionmentioning
confidence: 99%
“…Although DID may not be the perfect substitute for randomized control trials, it is a feasible way to understand causal relationships between the intervention and outcome [39]. This type of analysis was also considered in measuring the net effect of the nutrition-based intervention to estimate the change in dietary intake from baseline to end-line in the intervention and control arm in Kaur et al study [40].…”
Section: Plos Onementioning
confidence: 99%
“…[6] Prevention and control efforts have predominantly targeted individual behaviour change amongst high-risk groups, with mixed results in South Asian settings. [7][8][9][10][11][12] There is a need to develop and test population level interventions that create an enabling environment for the prevention of T2DM at scale, shifting from individualistic to structural and social interventions. [13] The DMagic (Diabetes Mellitus Action through community Groups or mHealth Information for better Control) trial used a participatory learning and action (PLA) approach directed at the general population in rural Bangladesh.…”
mentioning
confidence: 99%